Consensually Nonmonogamous Clients and the Impact of Mononormativity in Therapy - Cassidy, Taya; Wong, Gina (Canadian Journal of Counselling and Psychotherapy, 2018)
Discourse about mononormativity has increased substantially over the last decade, categorically naming and addressing a North American bias to unintentionally privilege monogamous relationships. The Canadian Counselling and Psychotherapy Association’s code of ethics (CCPA, 2007) outlines a need for counsellors to be sensitive to the diversity of all clients and to refrain from discrimination. The code suggests an ethical imperative to examine one’s values and attitudes when counselling clients who engage in consensual nonmonogamy (CNM). A paucity of understanding exists as to the potential impact a counsellor with a mononormative bias may have on the therapy process. Therapist assumptions, client perceptions, theoretical orientation, and clinical intervention strategies from the perspective of providing therapy to CNM clients will be discussed through a synthesis of the extant literature. Recommendations for counselling practice and suggestions for further research, as well as counselling education aimed at increasing counsellor competence when working with CNM populations, are provided. Implications of mononormativity on the Canadian counselling profession are highlighted.